Achieving Public Welfare through Tax Facilities On Foreign Grants For The Government Projects - Arsawan, I Gede Yudi (Fakultas Hukum Dehasen, 2025)
This study aims to identify tax facilities in the implementation of grants for government project purposes. Taxation serves as a crucial instrument in supporting economic growth and national development. Its budgetary function plays a vital role in ensuring sufficient state funds for financing government activities. Additionally, its regulerend function contributes to facilitating national economic growth, such as providing tax incentives for foreign grants aimed at government project implementation. Following the enactment of Minister of Finance Regulation Number 80 of 2024, provisions have been established to ease the granting of tax facilities for foreign grants intended for government projects. However, an analysis of the procedures and mechanisms for its application is necessary. The research method used in this study is normative juridical with a qualitative approach. This study found that government projects funded by foreign grants eligible for tax facilities under Minister of Finance Regulation Number 80 of 2024 have a broader scope compared to the definition of public interest projects, thus making the regulation applies lex specialis derogat legi generali. The tax facilities provided include value-added tax (VAT), sales tax on luxury goods, income tax, and as well import duties.